PRAGMATIC ANALYSIS OF POLITENESS STRATEGY IN SOCIAL MEDIA COMMUNICATION IN BIGMO YOUTUBE VIDEOS - Citra Nurjanah; Friska Ruth Margareth Purba; Sonya Trikandi; Fidiatun adiyan (STKIP Subang, 2026)
Social media communication serves not only as a means of conveying information but also as a medium that reflects the use of politeness strategies in maintaining interpersonal relationships. One example of such communication can be found in Bigmo's YouTube podcast, which features spontaneous and interactive conversations. This study aims to analyze the politeness strategies used in social media communication in Bigmo's YouTube video entitled